2022
DOI: 10.3390/foods11172564
|View full text |Cite
|
Sign up to set email alerts
|

Can the Part Replace the Whole? A Choice Experiment on Organic and Pesticide-Free Labels

Abstract: Chemical pesticides are a serious impediment to agricultural sustainability. A large-scale reduction in their use to secure food supplies requires more innovative and flexible production systems. Pesticide-free production standards bring together the strengths of all participants in the food value chain and could be the catalyst for this transition. Using a choice experiment approach and green tea as an example, this study investigated consumers’ preferences for organic and pesticide-free labels. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…Additionally, the educational levels and family members of this sample are similar to those reported in earlier organic food purchase intention studies (e.g., J. Wang et al, 2020; Zheng, Zeng et al, 2022). The majority of the sample (72.0%) reported that there was child and elder in their home.…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…Additionally, the educational levels and family members of this sample are similar to those reported in earlier organic food purchase intention studies (e.g., J. Wang et al, 2020; Zheng, Zeng et al, 2022). The majority of the sample (72.0%) reported that there was child and elder in their home.…”
Section: Methodssupporting
confidence: 77%
“…Organic food has gained the trust of Chinese consumers (Yang et al, 2021;Zheng, Wen, et al, 2022). The organic label serves as a signal to convey information about the quality and safety of products to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Branding is a unique symbol that distinguishes products from competitors and transmits quality information to consumers. It is a vital component in individual purchasing decisions and extrinsic attributes that signal quality and enhance individual trust (Zheng et al, 2022). Hence, customers are willing to pay a premium price for a preferred food product (Yin et al, 2019;Zheng et al, 2022).…”
Section: Choice Sets Designmentioning
confidence: 99%
“…It is a vital component in individual purchasing decisions and extrinsic attributes that signal quality and enhance individual trust (Zheng et al, 2022). Hence, customers are willing to pay a premium price for a preferred food product (Yin et al, 2019;Zheng et al, 2022). The implementation of brand labels in rice marketing can influence rice producers to improve and maximize product quality.…”
Section: Choice Sets Designmentioning
confidence: 99%
See 1 more Smart Citation